An empirical investigation of individual and team contests - Huang, Lingbo (2016)
This thesis presents an empirical investigation of individual and team contests using both lab experiments and field data. The thesis is comprised of five chap- ters. Chapter 1 introduces the overarching theme of this thesis and the common methodological tool, which is a novel real effort task used in the lab experiments. Chapter 2 discusses this real effort task in more detail and shows its usefulness in studying behavioural responses to incentives by presenting a series of experiments, including individual production with piece-rate incentives, team production, gift exchange, and tournament, using the task. All of the results are closely in line with theoretical predictions and, where applicable, the stylised facts from experiments using purely induced values. Chapter 3 experimentally examines the role of interpersonal comparisons in an individual contest. The experiment follows Gill and Prowse (2012) and is designed to investigate the source of disappointment aversion, that is, whether it is purely an asocial concept, akin to loss aversion, or fuelled by interpersonal comparisons. The new evidence however rejects predictions of the disappointment aversion model, both when interpersonal comparisons are possible and when they are not. Chapter 4 empirically examines strategic behaviour of contestants in a dynamic “best-of-three” team contest. I find evidence of “strategic neutrality” in both field data from high-stakes professional squash team tournaments and lab data from an experiment: the outcomes of previous battles do not affect the current battle. The lab data however reveal that the neutrality prediction does not perfectly hold at the level of individual efforts. Chapter 5 concludes the thesis by summarising all findings in previous chapters, discussing the limitations, and pointing to directions for future research.